An Empirical Assessment of the Proximity-Concentration Trade-off Between Multinational Sales and Trade - Brainard, S. Lael (American Economic Review, 1997)
This paper examines the extent to which multinational location decisions reflect a trade-off between achieving proximity to customers and concentrating production to achieve scale economies. It finds that overseas production by multinationals increases relative to exports the higher are transport costs and trade barriers and the lower are investment barriers and scale economies at the plant level relative to the corporate level. However, it is not possible to reject a model with only country and industry effects. The evidence also suggests that multinational activity is more likely the more similar are the home and foreign markets–contrary to conventional wisdom.